O processo transcriativo de São Bernardo de Leon Hirszman - Bozicanin, José Eduardo (2010)
The purpose of our research was to recoup some of the ideas about the intersemiotic translation of Graciliano Ramos' novel Sao Bernardo (1934) to the cinema. In this masters dissertation we realised the creative genesis of Leon Hirszman's filmmaking processes by following the path traced by the film-maker since the reading of the homonymous novel to the to the writing of an unknown script and posteriorly in his film editing and sonorization approaches.